Siblings with pierre robin sequence - Medhini Madi; Subhas G Babu; Sonika Achalli; Supriya Bhat; Kumuda Rao; Ananya Madiyal (Wolters Kluwer Medknow Publications, 2017)
Pierre Robin anomalad is a syndrome characterized by cleft of the palate, micrognathia of the mandible, and glossoptosis. This syndrome can occur as an individual presentation, or it may be associated with a wide variety of syndromes and anomalies. Such patients are burdened with several problems, some obvious and some less so. The most obvious problems such as the psychological difficulties the patients will have to face due to the appearance and associated problems such as feeding and speech difficulties and serious consequences such as airway obstruction. Here, we report two cases of Pierre Robin sequence seen in the same family in two children of the same parents.